The three-dimensional shapes of underground coal miners' feet do not match the internal dimensions of their work boots. Issue 4 (3rd April 2018) - Dobson, Jessica A.; Riddiford-Harland, Diane L.; Bell, Alison F.; Steele, Julie R.
Abstract: Mining work boots provide an interface between the foot and the ground, protecting and supporting miners' feet during lengthy coal mining shifts. Although underground coal miners report the fit of their work boots as reasonable to good, they frequently rate their boots as uncomfortable, suggesting that there is a mismatch between the shape of their feet and their boots. This study aimed to identify whether dimensions derived from the three-dimensional scans of 208 underground coal miners' feet (age 38.3 ± 9.8 years) differed from the internal dimensions of their work boots. The results revealed underground coal miners wore boots that were substantially longer than their feet, possibly because boots available in their correct length were too narrow. It is recommended boot manufacturers reassess the algorithms used to create boot lasts, focusing on adjusting boot circumference at the instep and heel relative to increases in foot length. Practitioner Summary: Fit and comfort ratings suggest a mismatch between the shape of underground coal miners' feet and their boots exists. This study examined whether three-dimensional scans of 208 miners' feet differed from their boot internal dimensions. Miners wore boots substantially longer than their feet, possibly due to inadequate width.